Narrative of the discoveries of the north coast of America [electronic resource] : effected by the officers of the Hudson's Bay Company during the years 1836-39 - Simpson, T. (Thomas), 1808-1840. (London : R. Bentley, 1843)
Tables. Electronic reproduction. Mode of access: Internet. 44